PENURUNAN KADAR COD AIR LIMBAH INDUSTRI PERMEN DENGAN MENGGUNAKAN REAKTOR LUMPUR AKTIF - ., Titiresmi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Pollution in the rivers is generally caused by domestic and industrial waste. SomeÃ‚Â treatments to solve it can be done individually or collectively. The effort can be physical,Ã‚Â chemical, or biological treatments chosen by its form, character, kind, quality, quantity.Ã‚Â PT Van Melle Indonesia is a candy company which produces a high biological waste with COD concentration 10000-30000 mg/litre. This paper reports activated sludge reactorÃ‚Â performance to decrease the wasteÃ¢â‚¬â„¢s organic content. The reactor is a biological wasteÃ‚Â water treatment, as a sequence of earlier anaerob process which still has a high CODÃ‚Â (700-4000 mg/litre). A continued reactor operation done with retention time variation 24Ã‚Â hours, 18 hours, 12 hours, and 6 hours show reduced COD varied 80-90%. The highestÃ‚Â efficiency was 97.59% from the 24 hours retention time, and the lowest efficiency was 89.5% from the 6 hours retention time.Ã‚Â Keywords: activated sludge reactor, candy industry wastewater